TRANSFORMASI PENDIDIKAN: PERAN MATA KULIAH PERENCANAAN TERHADAP KESIAPAN KOMPETENSI MENGAJAR CALON GURU FISIKA - Mirna Astuti; Ari Cahya Mawardi; Siti Fatonah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
A study was conducted to investigate the impact of a planning course on prospective teachers' professionalism in a Physics Education Study Program. Using a qualitative case study method, the study analyzed data from 5th semester students who took the course. The findings showed that the planning course not only equipped students with skills in developing lesson plans, but also boosted their confidence and readiness for real teaching experience. Additionally, the course encouraged students to engage in self-reflection, which is crucial for their professional development. The study suggests that higher education institutions should ensure the effective implementation of the planning course to produce competent teachers who are well-prepared to tackle the challenges of the education field.